A rare case of osteoblastoma in the femoral head combined with cam-type femoroacetabular impingement: A case report. (December 2020) - Morita, Akira; Kobayashi, Naomi; Choe, Hyonmin; Tezuka, Taro; Kawabata, Yusuke; Hayashida, Kenta; Higashihira, Shota; Kato, Ikuma; Inaba, Yutaka
Osteoblastoma is a relatively rare benign bone-forming tumor accounting for less than 1% of all bone tumors. This report describes a patient with an osteoblastoma in the femoral head complicated by coexistence of femoroacetabular impingement. A 25-year-old male rugby football player complained of severe right hip pain after an injury during rugby practice. The pain became progressively worse despite resting from sports activity and rehabilitation for 4 months. The image inspection revealed bone tumor complicated by cam-type femoroacetabular impingement and a labral injury. Hip arthroscopic surgery was planned using a navigation system and a three-dimensional model for both complete debridement and cam resection. The tumor was resected by open surgery using a posterior approach. The bone tumor was diagnosed histopathologically as an osteoblastoma. The patient's symptoms improved markedly after surgery, with no evidence of local tumor recurrence or hip arthritis 1 year later.